The brain-penetrating CXCR4 antagonist, PRX177561, increases the antitumor effects of bevacizumab and sunitinib in preclinical models of human glioblastoma. Issue 1 (December 2017) - Gravina, Giovanni; Mancini, Andrea; Marampon, Francesco; Colapietro, Alessandro; Delle Monache, Simona; Sferra, Roberta; Vitale, Flora; Richardson, Peter; Patient, Lee; Burbidge, Stephen; Festuccia, Claudio
Abstract Background Glioblastoma recurrence after treatment with the anti-vascular endothelial growth factor (VEGF) antibody bevacizumab is characterized by a highly infiltrative and malignant behavior that renders surgical excision and chemotherapy ineffective. It has been demonstrated that anti-VEGF/VEGFR therapies control the invasive phenotype and that relapse occurs through the increased activity of CXCR4. We therefore hypothesized that combining bevacizumab or sunitinib with the novel CXCR4 antagonist, PRX177561, would have superior antitumor activity. Methods The effects of bevacizumab, sunitinib, and PRX177561 were tested alone or in combination in subcutaneous xenografts of U87MG, U251, and T98G cells as well as on intracranial xenografts of luciferase tagged U87MG cells injected in CD1-nu/nu mice. Animals were randomized to receive vehicle, bevacizumab (4 mg/kg iv every 4 days), sunitinib (40 mg/kg po qd), or PRX177561 (50 mg/kg po qd). Results The in vivo experiments demonstrated that bevacizumab and sunitinib increase the in vivo expression of CXCR4, SDF-1α, and TGFβ1. In addition, we demonstrate that the co-administration of the novel brain-penetrating CXCR4 antagonist, PRX177561, with bevacizumab or sunitinib inhibited tumor growth and reduced the inflammation. The combination of PRX177561 with bevacizumab resulted in a synergistic reduction of tumor growth with an increase of disease-free survival (DSF) and overall survival (OS), whereas the combination of PRX177561 with sunitinib showed a mild additive effect. Conclusions The CXC4 antagonist PRX177561 may be a valid therapeutic complement to anti-angiogenic therapy, particularly when used in combination with VEGF/VEGFR inhibitors. Therefore, this compound deserves to be considered for future clinical evaluation.